Laser OptoAcoustic Tomography: Towards New Technology for Biomedical Diagnostics - Su, Richard (2012)
This paper provides a short review of physical principles, technology, biomedical applications and perspectives of the optoacoustic imaging. Ideas that made this rapidly developing field possible include the following: (1) laser pulses may be effectively used to produce acoustic pressure in biological tissues localized to the areas of increased optical absorption, (2) the resulting acoustic (ultrasonic) waves propagate in tissues with minimal distortions and attenuation, (3) 2D and 3D maps (images) of the absorbed optical energy can be reconstructed with high resolution from the detected optoacoustic signals. Modern optoacoustic imaging systems include scanning focused transducers and 2D/3D transducer arrays. The widely accepted 2D arrays are employed either for real-time 2D optoacoustic imaging or for 3D imaging via translational or rotational scanning. A commercial prototype of a 3D OAT system is being developed by TomoWave Labs where major biomedical applications include visualization of specific targeting using exogenous optoacoustic contrast agents and imaging of blood distribution and oxygentaion status can be investigated.